Flame, Combustion and Explosion Thermometry : From optimising waste incineration to internal combustion engines and defence applications. Issue 1 (28th January 2023) - Fateev, Alexander
Flame is a natural phenomenon and is a basic element of any combustion process. The majority of flames consist of a gas; there is, however, a small amount of ionisation occurring in the flame. Despite the increased focus on combustion-free energy production such as wind, air and water power, and the refocus on nuclear energy now considered to be carbon-free, nonetheless combustion will remain, for the next few decades, the major energy and heat production route worldwide. Apart from carbon dioxide, which is commonly considered to be the major pollutant, there are other gases like nitric oxide and nitrogen dioxide which, although found in significantly lower amounts in the exhaust gases from combustion units, still present a large environmental impact and are a concern. There are however well-established technologies for removing combustion products from the exhaust gas, and the combustion process can in general be made CO2 and environmentally neutral. Combustion optimisation is a route for further reduction of undesirable byproducts, fuel consumption minimisation and finally an overall energy and heat production enhancement. The key parameter in any combustion process is reliable flame and (post-) combustion gas temperature measurement and control. Various combustion environments such as waste incineration, internal combustion engines or solids explosions cause the appearance of various optical emission features in different spectral ranges not accessible to the human eye. A combination of modern and newly developed fast spectral optical techniques with extensive theoretical developments in spectral and heat radiative transfer modelling allows us to obtain detailed snapshots of what is happening in the combustion process. That also gives a possibility to establish a direct link to the industrial process control and pollutant emission reduction. In this article some examples of in situ flame and gas temperature measurements in various combustion environments and advanced spectral modelling are given and perspectives for further commercial instrumentation developments are discussed.